Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.31989/ffhd.v7i1.279
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress affects bioactive compounds in potatoes (Solanum tuberosum L.) relevant to non-communicable diseases

Abstract: Background: Potatoes react very sensitive to drought during growth, and appropriate plant stress responses may affect metabolites associated with the health quality of tubers.Objective: The aim of this study is to determine the effects of drought stress (DS) on soluble sugars, starch, crude protein, minerals, free amino acids (AAs) and fatty acids (FAs).Design: The experiment was carried out on three potato genotypes during two years with four replications. The plants were grown in pots, in a glasshouse with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
3
7
1
Order By: Relevance
“…The macronutrient contents in tubers of very early potato cultivars tested were similar, except Mg. Tubers of 'Miłek' contained lower Mg than 'Denar' and 'Lord'. Wegener et al [38] reported that K, P, and Mg content in potato tubers increased, while Ca content reduced as a result of drought stress, which was not confirmed in the present study. According to Mazurczyk and Lis [39], weather conditions during potato growth have no effect on macronutrient content in tubers.…”
Section: Discussioncontrasting
confidence: 93%
“…The macronutrient contents in tubers of very early potato cultivars tested were similar, except Mg. Tubers of 'Miłek' contained lower Mg than 'Denar' and 'Lord'. Wegener et al [38] reported that K, P, and Mg content in potato tubers increased, while Ca content reduced as a result of drought stress, which was not confirmed in the present study. According to Mazurczyk and Lis [39], weather conditions during potato growth have no effect on macronutrient content in tubers.…”
Section: Discussioncontrasting
confidence: 93%
“…In the present study, the conditions of used stress were characterised by high intensity of severity according to average relative water content in leaves RWC 73.23% for DS and 87.10% for WLS. In both milder or severer conditions of two years, Wegener et al (2017) observed an increase of sucrose and a decrease of glucose and fructose in three potato genotypes.…”
Section: Resultsmentioning
confidence: 84%
“…Considering drought stress influence on fruit quality, water had a significant effect on carbon partitioning at fruit maturation, whereas the intensity of metabolic changes increases as fruit ripens during the final slow growth period, when glucose and fructose continue to accumulate, and the concentration of soluble sugars reaches a maximum (Luo, Kang, & Chen, 2020). Drought stress impact on potato tuber yield and quality was assessed by Wegener, Jurgens, and Jansen (2017), who reported an increase in free amino acids, α‐linolenic acid, myo‐inositol and minerals like magnesium, potassium and phosphorus in tubers of drought‐stressed plants. The authors highlighted proline, an osmoprotectant in plants, as amino acid which plays significant roles in human nutrition, through protein metabolism, particularly in the synthesis of arginine, polyamines and glutamate, in addition to wound healing processes and immune responses.…”
Section: Plant Response To Abiotic Stress and Biostimulant Applicationmentioning
confidence: 99%